Correlated effects of sperm competition and postmating female mortality - Civetta, Alberto (The National Academy of Sciences, 2000)
Adaptations in one sex may impair fitness in the opposite sex. Experiments with Drosophila melanogaster have shown that seminal fluid from the male accessory gland triggers a series of postmating responses in the female, including increased egg laying rate and lower remating propensity, but that accessory gland proteins also increase female death rate. Here, we tested the relationships among the longevity of females mated to males from 51 chromosome-extracted D. melanogaster lines, male-mating ability, and sperm-competitive ability. We found significant differences in longevity of females mated to males of different genotypes, and all mated females showed a higher death rate than control virgin females shortly after mating. Both the age-independent mortality parameter (the intercept of the female's survival function) and the slope of the mortality rate curve were significantly correlated with the proportion of progeny sired by the first male to mate relative to tester males (sperm-defense ability, P1). No significant correlation was found between the proportion of progeny sired by the second-mating male relative to tester males (sperm-offense ability, P2) and any mortality parameter. Our results support the hypothesis of a tradeoff between defensive sperm-competitive ability of males and life-history parameters of mated females.